Criminological Examination of Physical and Psychological Violence Committed Against Children in the School Environment - Imran, Mohamad Fadil (Universitas Syiah Kuala, 2024)
The phenomenon of violence against children often occurs in schools, both in the form of physical and psychological violence. This is widely seen on social media, leading to a sense of concern. Consequently, it requires special attention from both schools and the government, directly reflected in various policies that, if properly implemented, can be applied to minimize these issues. Therefore, it is important for researchers to conduct an examination of the etiology and the urgency of criminal policies related to physical and psychological violence carried out by children in the school environment. This study aims to analyze the causes and prevention efforts, as well as the mitigation of criminal acts of physical and psychological violence carried out by children against other children. The research findings indicate that, (1) Children tend to easily learn and apply what they see, including bullying behavior. A child who engages in violence, whether physical or psychological, tends to have witnessed or experienced being a victim of such violence, prompting them to replicate such behavior. (2) Efforts to mitigate physical and psychological violence can employ penal (criminal law) and non-penal (outside criminal law) policies. Prevention efforts can be carried out by teaching children about the consequences of physical and psychological violence, their rights when subjected to such violence, and raising awareness among children who perpetrate physical and psychological violence by instilling in them the belief that such actions are reprehensible and detested by everyone.